17β-Estradiol Treatment Attenuates Neurogenesis Damage and Improves Behavior Performance After Ketamine Exposure in Neonatal Rats - Li, Weisong; Li, Huixian; Wei, Haidong; Lu, Yang; Lei, Shan; Zheng, Juan; Lu, Haixia; Chen, Xinlin; Liu, Yong; Zhang, Pengbo (Frontiers in Cellular Neuroscience, 2019)
Ketamine exposure in the developing brain disturbed normal neurogenesis and resulted in subsequent neurocognitive deficits. 17β-estradiol provides robust neuroprotection in a variety of brain injury models in animals of both sexes and attenuates neurodegeneration induced by anesthesia agents. In the present study, we investigated whether 17β-estradiol could attenuate disturbed neurogenesis and behavioural deficits induced by ketamine exposure in neonatal rats. Sprague-Dawley rats at postnatal day (PND) 7 and neural stem cells (NSCs) were treated with either normal saline, ketamine, or 17β-estradiol prior/after ketamine exposure, respectively. The rats were decapitated at PND14 for detection of neurogenesis in the subventricular zone (SVZ) and subgranular zone (SGZ) of the hippocampus by immunostaining. NSC proliferation, neuronal differentiation, and apoptosis were assessed by immunohistochemistry and TUNEL, respectively. The protein expressions of caspase-3 in vivo and GSK-3β, p-GSK-3β in vitro were assessed by western blotting. Spatial learning and memory abilities were measured by the Morris water maze test at PND 42-47. Ketamine exposure decreased cell proliferation in the SVZ and SGZ, inhibited NSC proliferation and neuronal differentiation, promoted NSC apoptosis and led to late cognitive deficits. Furthermore, ketamine increased caspase-3 expression in vivo and decreased protein expressions of p-GSK-3β in vitro. Treatment with 17β-estradiol attenuated ketamine-elicited changes both in vivo and in vitro. We for the first time showed that 17β-estradiol alleviated ketamine-induced neurogenesis damage and neurocognitive deficits in developing rat brain. Moreover, the protection of17β-estradiol is associated with the GSK-3β.